Chronic Nasal Congestion - B. N., Toshmamatov; N. E, Djumanova (American Journal of Bioscience and Clinical Integrity, 2025)
Chronic nasal congestion is a long-lasting condition characterized by persistent obstruction of the nasal passages due to inflammation, mucosal swelling, or structural abnormalities. It is not a disease itself but a symptom commonly associated with various underlying disorders such as chronic rhinitis, sinusitis, nasal polyps, deviated nasal septum, or allergic reactions. The main pathophysiological mechanisms include prolonged inflammation of the nasal mucosa, vascular dysregulation, and mucous hypersecretion. Common causes are allergic rhinitis, non-allergic (vasomotor) rhinitis, chronic sinus infections, environmental irritants, and prolonged use of nasal decongestant sprays. Clinical manifestations include difficulty in nasal breathing, mouth breathing, snoring, reduced sense of smell, and postnasal drip. Chronic congestion significantly impairs sleep quality, cognitive function, and overall quality of life. Diagnosis is based on clinical evaluation, nasal endoscopy, allergy testing, and imaging studies when structural causes are suspected. Treatment depends on the etiology and may include intranasal corticosteroids, antihistamines, saline irrigation, surgical correction, or allergen immunotherapy. Timely identification and management of chronic nasal congestion are essential to prevent complications such as chronic sinusitis, otitis media, and sleep-disordered breathing.